2020
DOI: 10.2151/jmsj.2020-043
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Classification of Heavy Rainfall Areas and their Characteristic Features in Japan

Abstract: We propose a new procedure for the objective identification and classification of heavy rainfall areas (HRAs) to advance the understanding of mesoscale convective systems (MCSs) in Japan. The distributions of accumulated precipitation amounts are evaluated from the radar/raingauge-analyzed precipitation amounts and characteristic features of HRAs are examined. The HRAs extracted during the warm seasons (April-November) in 2009-2018 are classified into four types (e.g., linear-stationary, linear, stationary, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…First, QSCBs in each event were objectively extracted using the method of Hirockawa et al (2020a), which identified and classified heavy rainfall areas into four types (linear-stationary, linear, stationary, and others) with defining criteria such as aspect ratio, overlap ratio, and duration from distributions of accumulated three-hour precipitation amounts derived from the Japan Meteorological Agency (JMA) radar/raingauge-analyzed precipitation amounts (RA; Nagata 2011). In this study, linear-stationary heavy rainfall areas were extracted as QSCBs (details are described by Hirockawa et al 2020a, b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, QSCBs in each event were objectively extracted using the method of Hirockawa et al (2020a), which identified and classified heavy rainfall areas into four types (linear-stationary, linear, stationary, and others) with defining criteria such as aspect ratio, overlap ratio, and duration from distributions of accumulated three-hour precipitation amounts derived from the Japan Meteorological Agency (JMA) radar/raingauge-analyzed precipitation amounts (RA; Nagata 2011). In this study, linear-stationary heavy rainfall areas were extracted as QSCBs (details are described by Hirockawa et al 2020a, b).…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that heavy rainfall occurs in Kyushu during the Baiu season, the rainy season from mid-to late spring through early to midsummer in Japan (e.g., Akiyama 1973;Ogura et al 1985;Nagata and Ogura 1991;Moteki et al 2004a, b), and quasi-stationary convective bands (hereafter QSCBs) often cause localized heavy rainfall (Ogura 1991;Yoshizaki et al 2000;Kato 1998Kato , 2005Kato , 2006. Statistical studies have indicated that precipitation systems corresponding to QSCBs occur frequently in Kyushu (Tsuguti and Kato 2014;Unuma and Takemi 2016a;Hirockawa et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…JMA have been operating R/A since 1988 to measure nationwide rainfall distribution and to prevent rainfall-related disasters across Japan (Makihara et al 1996;Shimpo 2001). R/A is well known as accurate rainfall product based on 5-minutely original radar data with a spatial resolution of ≈1 km that were calibrated by a dense network of rain gauge data via the Automated Meteorological Data Acquisition System (AMeDAS) (Makihara et al 1996;Kamiguchi et al 2010;Urita et al 2011;Ishizaki and Matsuyama 2018;Hirockawa et al 2020). Although hourly rainfall accumulation of weather radar underestimates hourly rain gauge readings by <10%, there is a high agreement with daily measurements by rain gauge data (Suzuki et al 2017).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Landslides occurred generally in hollows in headwaters with a size in the order of 10 2 −10 3 m 2 scale for their source area. Both of the events occur in southwestern Japan, where heavy rainfall is common due to frequent frontal storms and tropical cyclones (Ozturk et al 2019;Hirockawa et al 2020). The rainfalls in 2017 (Fukuoka) and 2018 (Hiroshima) were also caused by mainly frontal storms after the passage of a tropical cyclone with a short-term intense rainfall over a small area in Fukuoka and a long-lasting heavy rainfall over a large area in Hiroshima (Tsuji et al 2020), with maximum hourly rainfall intensity breaching 60 mm (30 mm) in Fukuoka (Hiroshima).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Recently, band-shaped areas of heavy rainfall caused by such quasi-stationary precipitation systems were named "senjo-kousuitai" in Japanese (Kato 2020). To understand the statistical characteristics of areas of heavy rainfall in Japan, including senjo-kousuitai, Hirockawa et al (2020a) objectively identified and classified areas of heavy rainfall into four types (i.e., linear-stationary, linear, stationary, and others) on the basis of the spatiotemporal continuity of the 3-h accumulated precipitation. They demonstrated that most areas of linear-stationary type were produced by typical elongated and stagnated precipitation systems that represent senjo-kousuitai.…”
Section: Introductionmentioning
confidence: 99%